2020
DOI: 10.1186/s12955-020-01484-z
|View full text |Cite
|
Sign up to set email alerts
|

Health-related quality of life in women with polycystic ovary syndrome attending to a tertiary hospital in Southeastern Spain: a case-control study

Abstract: Background: Polycystic ovary syndrome (PCOS) is a chronic condition with symptoms affecting many women at reproductive age and evaluating their health-related quality of Life (HRQoL) is an important issue. Moreover, differences in the HRQoL between women with different PCOS phenotypes have never been analyzed. Therefore, the aim of our study was to compare the HRQoL between women with PCOS-and its phenotypes-and controls attending to a tertiary hospital. Methods: A group of 117 women with PCOS and 153 controls… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
18
1
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 41 publications
(60 reference statements)
4
18
1
2
Order By: Relevance
“…Exclusion criteria were pregnancy or lactating, oncological treatment, hormonal medication during the three months prior to the study, genitourinary prolapse or endocrine disorders ( n = 5). Methods were explained in previous works [ 35 , 36 , 37 , 38 ]. Figure 1 shows the number of participants and the exclusion criteria.…”
Section: Methodsmentioning
confidence: 99%
“…Exclusion criteria were pregnancy or lactating, oncological treatment, hormonal medication during the three months prior to the study, genitourinary prolapse or endocrine disorders ( n = 5). Methods were explained in previous works [ 35 , 36 , 37 , 38 ]. Figure 1 shows the number of participants and the exclusion criteria.…”
Section: Methodsmentioning
confidence: 99%
“…Wśród objawów klinicznych PCOS, które w największym stopniu wpływają na jakość życia pacjentek, należy wyróżnić otyłość, owłosienie typu męskiego, trądzik, zaburzenia miesiączkowania oraz niepłodność [14]. Badania własne wykazały, że nadmierna masa ciała występowała u ponad połowy pacjentek, a średnia wartość BMI odpowiadała nadwadze, co zostało potwierdzone przez innych badaczy [15][16][17][18][19][20]. Uzyskane wyniki odbiegały jednak znacząco od tych przedstawionych przez S. Sidra i wsp.…”
Section: Dyskusjaunclassified
“…Sánchez-Ferrer i wsp. (2020) [16], podczas gdy odsetek kobiet przyjmujących napoje alkoholowe co najmniej raz w tygodniu był taki sam jak odsetek uzyskany w badaniach B. Zhang i wsp. (2020) [19].…”
Section: Dyskusjaunclassified
“…Asian Muslim women with PCOS migrated to Austria were faced greater psychological problems [35] while another study on PCOS women from Brazil reported the psychological distress positively associated with changes in appearance like obesity, acne and hirsutism [36]. Lately studies from Spain [37] and UK have shown the prominent concern about weight and infertility among PCOS women [38] and re ected the poor quality of life among PCOS women with overweight or obesity [30].…”
Section: Discussionmentioning
confidence: 99%